Students’ Perception In Using Powtoon Software Program To Enhance Their Ability In Learning English In Bumigora University - Lela Rahmawati; Erwin Suhendra; Sutarman Sutarman (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
21st Century learning is learning that integrates literacy skills, knowledge skills, skills and attitudes, as well as mastery of technology. Therefore, in the 21st century, mastery of technology and learning are closely related. Technology can also be connected to language learning. With the development of the internet and technology, many companies have created free and paid applications and software to support the learning process.One of the applications that can be used in learning English is Powtoon. PowToon is a tool whose operation is similar to Power Point, Impress, or even Prezi. It uses slides to which text and images can be added to, but it also allows animation and the incorporation of sound or music, available in the same application or through an external source. This reasearch used a qualitative case study and used preeliminary data, structured interviews, and Questionnaire. The findings of the research showed students’ perceptions on the use of Powtoon in EFL classroom were: 1) Students’ Perceptions on Powtoon Helps Students in increasing English Achievements, Powtoon could be a solution to enhance EFL students' English skills to have good communication skill in the learning process. Powtoon has many beneficial features such text, music, animation, characters, and audio-visual for EFL students in enhancing their English skills, such as listening, speaking, reading, and writing,2)Students’ Perceptions on Powtoon as an Fascinating Application, Powtoon as an interesting application because there are a lot of animation, sound, and images. 3) Students’ Perceptions on Powtoon Increasing Students’ Interactive and Motivation, this application shows that learning descriptive text through the animation video from PowToon software make the learning process more interesting, and it can help students’ understanding to the material